Strategi Dakwah Lembaga Perhimpunan Bawe Paser dalam Meningkatkan Kegiatan Keagamaan di Kabupaten Penajam Paser Utara, Kalimantan Timur - Putri Anggun Asprilia (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the da'wah strategy implemented by the Bawe Paser Association to increase religious activities in North Penajam Paser Regency, East Kalimantan, and to identify the obstacles encountered in its implementation. This study used a qualitative approach with field research. Data were collected through observation, in-depth interviews, and documentation of administrators, members, and the community around the institution. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing. The results show that the da'wah strategy implemented by the institution includes a participatory approach through various religious activities, such as regular religious study groups, mental development, community service, Ramadan safaris, and Islamic holiday commemorations that directly involve the community. Obstacles faced include limited funds, unprofessional human resources, and low participation of some members. These findings indicate that community-based and local culture-based da'wah strategies play a significant role in increasing community religious activities. The implications of this study emphasize that strengthening institutional capacity, increasing member participation, and providing resource support are essential for da'wah strategies to be more effective and sustainable in the community.